The strength of collusion: A conceptual framework for interpreting hybrid social orders - Dewey, Matias (2016)
By moving away from dualistic perspectives that see social order as the product of strong states but not weak states, this article develops a conceptual framework for interpreting hybrid social orders, i.e. those established by both legal and extra-legal actors. The initial premise is that hybrid forms of social domination resulting from the interaction between legal and extra-legal actors, and regulated by a combination of rational bureaucratic and neo-patrimonial rules, produce relevant economic and political outcomes such as job creation, the supply of basic services and the production of authority. Especially in contexts of continuous economic crisis, ethnic segregation, social marginalization and persistent inequality, these outcomes have ordering effects both in terms of reducing uncertainty and regulating social expectations. Furthermore, in such social contexts, socially tolerated illegal markets play a decisive role. Supported by recent and innovative research, this article concludes with hypotheses intended to promote further research.